Confessing sex in online student communities. (December 2017) - Dominguez-Whitehead, Yasmine; Whitehead, Kevin A.; Bowman, Brett
Highlights: Online Facebook "Confessions" sites from two countries are examined. A Foucauldian framework, emphasizing the centrality of sex and sexuality, is used. Conversation analysis is employed to examine participants' posts on the sites. Normative sexuality is (re)produced and/or contested through participants' actions. Abstract: In this paper, we examine Facebook "Confessions" sites associated with two large universities (one North American and one South African) to investigate the ways in which students interactionally negotiate normativity in discussions initiated by confessions relating to sex. The research is grounded in a Foucauldian framework that emphasizes the centrality of sex and sexuality. Our findings focus on two interrelated aspects of the data. The first concerns the features of the initial (anonymous) confessional posts, and the second relates to subsequent comments on the initial post. Close examination of initial posts offers insights into participants' orientations to sexual acts, situations and beliefs that are treated as either normative or transgressive. Subsequent comments posted by participants reveal ways in which the "confessability" of confessions is interactionally ratified or contested. The findings thus demonstrate some ways in which normative sexuality is (re)produced, ratified, and contested within student online communities.